Hubungan Pemahaman Keselamatan dan Kesehatan Kerja (K3), Kedisiplinan Mahasiswa, dan Bimbingan Dosen terhadap Unjuk Kerja Praktik Mahasiswa Program Studi Teknik Mesin Politeknik Negeri Padang - Fardinal Fardinal; Nizwardi Jalinus; Hendri Hendri (Politeknik Negeri Padang, 2018)
The problem in this research was the low performance of student in the Practical of Mechanical Workshop Mechanical Engineering Study Program Polytechnic State of Padang in the implementation of learning practices that affected by occupational safety and health , student discipline, and guidance of lecturer. This study aims to analyze the relationship occupational safety and health, student discipline and guidance of lecturer with the student practice performance of mechanical workshop Mechanical Engineering Study Program Polytechnic State of Padang. This study was a correlational study with a quantitative approach. The population of the research is all the student of 2016 with consisted of 125 people. The sampling technique used is proportional random sampling, that 96 people as a sample and 29 people were respondents taken from the population. Data were collected through a questionnaire that had been tested for validity and reliability. The results showed that, 1) there is a strong and positive correlation between occupational safety and health with the student practice performance with rhitung (0.463)> rtabel (0,199); 2) There is a strong and positive correlation between discipline with performance of students practical with rhitung (0.479)> rtabel (0,199); 3) There is a strong and positive relationship between the guidance of lecturers with the performance of student practical with rhitung (0.451)> rtabel (0,199); 4) there is a very strong and positive together occupational safety and health discipline students and guidance of the lecturer with the performance of student practical rhitung (0.525)> rtabel (0,199).